(untitled) (Bangladesh Journal of Infectious Diseases, 2022)
Background: The burden of COVID-19 infection in children is lesser than adult; however, there are only a few data describing COVID-19 in pediatrics. Objective: The purpose of the present study was to determine the clinical characteristics and early outcomes of children with COVID-19 infection admitted to children Hospital in Dhaka city. Methodology: This is a prospective observational study included children of RT-PCR positive COVID-19 cases admitted to Dr. MR Khan Shishu Hospital & ICH between June2020 to November 2020. A total 95 children were enrolled. Patients were categorized clinically and visited every day during their hospital stay. This study included mode of presentation, the pattern of comorbidities, presence of co-infection, clinical trajectory & early outcomes. Clinical outcomes included survival, duration of oxygenation, lengths of hospital stay. Data were analyzed after collection of demographic and clinical data of 95 enrolled children. Results: Among 95 children with COVID-19 admitted to Dr. M R Khan Shishu Hospital & ICH, 56 (58.95%) were male and 39(41.05%) were female. Maximum 35 (36.84%) of the patients were between 1-5 years age group. 65 (68.42%) presented with respiratory symptoms and 19 (20%) presented with gastrointestinal symptoms. Twenty-five patients (26.32%) had significant preexisting comorbidities. Most common symptoms were fever 73(76.84%), cough 65(68.42%), sore throat 24(25.26%), diarrhea 21(22.11%). Oxygenation was required for 5 patients (5.26%). 1 patient (0.95%) had died and 1required ventilatory support in ICU. The median (range) hospital lengths of stay was 7(3-14) days. Conclusion: Most of the children with COVID-19 presented with mild to moderate symptoms & gastrointestinal symptoms were not uncommon. Most of the patients had good prognosis and only few patients required respiratory support. Bangladesh Journal of Infectious Diseases, April 2022;9(Suppl_1): S9-S13